2022
DOI: 10.1088/1752-7163/ac5f13
|View full text |Cite
|
Sign up to set email alerts
|

Engineering solutions to breath tests based on an e-nose system for silicosis screening and early detection in miners

Abstract: Objectives: This study aims to develop an engineering solution to breath tests using an electronic nose (e-nose), and evaluate its diagnosis accuracy for silicosis. Influencing factors of this technique were explored. Methods: 398 non-silicosis miners and 221 silicosis miners were enrolled in this cross-sectional study. Exhaled breath was analyzed by an array of 16 organic nanofiber sensors along with a customized sample processing system. Principal Component Analysis was used to visualize the breath data, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…The VGG16 and ResNet18 model network architecture details are provided in the Supporting Information. Using the strategy of natural learning rate reduction, it can be seen that the loss value of the VGG16 model basically remains stable after undergoing 60 epoch training with no significant increase in accuracy. And at the end of the training, it showed a greater loss state .…”
Section: Results and Discussionmentioning
confidence: 99%
“…The VGG16 and ResNet18 model network architecture details are provided in the Supporting Information. Using the strategy of natural learning rate reduction, it can be seen that the loss value of the VGG16 model basically remains stable after undergoing 60 epoch training with no significant increase in accuracy. And at the end of the training, it showed a greater loss state .…”
Section: Results and Discussionmentioning
confidence: 99%
“…No studies have been published on early detection of ILD using an eNose, except for two studies that focus on pneumoconiosis screening in high risk groups [ 15 , 16 ]. Although these were pilot studies, they found high accuracies when comparing people with and without pneumoconiosis.…”
Section: Discussionmentioning
confidence: 99%
“…In ILD, breath profiles of patients could be differentiated from healthy controls [ 10 14 ] and individual ILDs from COPD [ 11 , 12 ]. Exploratory studies in pneumoconiosis show the potential of using an eNose for screening purposes in ILD [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…As for electroanalytical devices, they are well suited for continuous monitoring, or clinical point-of-care (POC) use at home or in hospitals. 12 A wide variety of gas sensing technologies were developed (e.g., resistive, capacitive). Capacitive sensors are static devices 13 that do not consume high power for sensing and are capable of working at room temperature (RT) with good linearity compared with resistive sensors, despite limitations in the response speed and limit of detection.…”
mentioning
confidence: 99%
“…Hence, they are not suitable for real-time monitoring. As for electroanalytical devices, they are well suited for continuous monitoring, or clinical point-of-care (POC) use at home or in hospitals . A wide variety of gas sensing technologies were developed (e.g., resistive, capacitive).…”
mentioning
confidence: 99%